2021
DOI: 10.1186/s12885-021-08142-7
|View full text |Cite
|
Sign up to set email alerts
|

Normal and cancer fibroblasts differentially regulate TWIST1, TOX and cytokine gene expression in cutaneous T-cell lymphoma

Abstract: Background Mycosis fungoides (MF) is a primary cutaneous T-cell lymphoma (CTCL) that transforms from mature, skin-homing T cells and progresses during the early stages in the skin. The role of the skin microenvironment in MF development is unclear, but recent findings in a variety of cancers have highlighted the role of stromal fibroblasts in promoting or inhibiting tumorigenesis. Stromal fibroblasts are an important part of the cutaneous tumor microenvironment (TME) in MF. Here we describe stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…Furthermore, Morimura et al [44] described an increase of the marker levels as the disease progressed, a finding also observed in our cases. Indeed, in our analysis, the increase in TOX expression in advance-phase disease as well as the higher TOX expression in A+ and DOD patients when compared to A− ones corroborate the hypothesis that TOX may be regarded more as a prognostic than as a diagnostic marker [6,8,51,52]. Such evidence may be emphasized by the decrease in TOX levels in two patients (no 14 and 18) who had a relapse in early-stage patch after TSEBI+bexarotene treatment with a decreased expression in TOX levels.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, Morimura et al [44] described an increase of the marker levels as the disease progressed, a finding also observed in our cases. Indeed, in our analysis, the increase in TOX expression in advance-phase disease as well as the higher TOX expression in A+ and DOD patients when compared to A− ones corroborate the hypothesis that TOX may be regarded more as a prognostic than as a diagnostic marker [6,8,51,52]. Such evidence may be emphasized by the decrease in TOX levels in two patients (no 14 and 18) who had a relapse in early-stage patch after TSEBI+bexarotene treatment with a decreased expression in TOX levels.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, five genes have been obtained for the HCC prognostic model. ACTA2 , actin alpha 2, which contributed to cell-generated mechanical tension and maintenance of cell shape and movement, was highly expressed in carcinomas [ 24 ]. Meanwhile, a previous study showed that CAFs enhanced the tumor-initiating and tumorigenic properties of HCC cells, and ACTA2 was exactly a biomarker of CAFs.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor-derived exosome, shuttle miR-375, polarized CAFs into aSMA, CXCL2, and IL-1b-expressing phenotypes, promoting tumor growth by decreasing p53 pathway-related gene expression in Merkel cell carcinoma [ 103 ]. In mycosis fungoides, CAFs derived from mycosis fungoides increased the expression of GATA3 (Th2 marker), as well as TWIFT1 and TOX (also used as a biomarker gene for the progression of mycosis fungoides), in CTCL cells [ 104 ] Overall, these reports suggest the possible mechanisms of crosstalk between tumor cells and CAFs in the development of the tumor microenvironment in non-melanoma skin cancers.…”
Section: Profiles Of Tumor-infiltrating Leukocytes Determine the Char...mentioning
confidence: 99%